Humeral Condylar Fractures in French Bulldogs—Inciting Cause and Factors Influencing Complications of Internal Fixation in 136 Dogs - Condon, Anna; Keeley, Ben; Midgley, Duncan; Butterworth, Steven; Schofield, Imogen; Bright, Steven (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective To report the inciting cause and configuration of humeral condylar fractures in French Bulldogs, and to identify risk factors for complications associated with their surgical stabilization, as well as their occurrence.Study Design Retrospective multicenter clinical cohort study.Animals French bulldogs (n = 136) with humeral condylar fracture.Methods Records from eight United Kingdom referral centers were reviewed for French bulldogs that underwent surgery for humeral condylar fracture between January 2017 and January 2021.Results Lateral fractures of the humeral condyle represented two-thirds of condylar fractures in this study (95 elbows; 69.8%); medial fractures of the humeral condyle and intracondylar Y or T fractures affected 22 (16.2%) and 19 (14%), respectively. A fall was the inciting cause for 60 elbows (45.6%), with stairs implicated in 27 (20.45%) elbows. Skeletal immaturity was significantly correlated with fracture. Complications affected 30 out of 132 dogs (136 elbows) (22%), of which 10 (33%) were major, and 20 (66%) were minor. Fixation method did not significantly impact complication rate for medial or lateral fractures of the humeral condyle (p = 0.87). Comminution increased the risk of complication for all humeral condylar fracture types (p = 0.02).Clinical Relevance Fixation method was not found to significantly impact the complication rate of surgically managed fractures of the humeral condyle in French bulldogs. Stair use, falling from low heights, and skeletal immaturity were common inciting reasons for humeral condylar fractures.
Keywords: French bulldogs; humeral condylar fractures; surgery; postoperative; complications